Understanding small-firm reactions to free trade agreements: Qualitative evidence from New Zealand. Issue 2 (13th May 2014) - Battisti, Martina; Jurado, Tanya; Perry, Martin
Abstract : Purpose: – Despite the proliferation of free trade agreements (FTAs) internationally, the limited research available on the subject indicates that few SMEs consider the existence of these agreements as a reason to engage in international markets or expand their existing international engagement. The purpose of this paper is to identify and augment SME international marketing models building on Merrilees and Tiessen's (1999) work; and to explain how these marketing models condition the reaction of small firm exporters to FTAs. Design/methodology/approach: – This study comprised in-depth interviews with 51 SME exporters in New Zealand. Participants were selected purposefully and were interviewed in a face-to-face, semi-structured format. Findings: – Five international marketing strategies were identified drawing on prior models of international marketing: sales-driven, relationship-driven, international boutique, arbitrager and market seeder. These models are characterised by different relationships to markets and to buyers served, and by the extent of customisation in the export offering. By using these models the authors analyse why SMEs have yet to significantly capitalise on the opportunities provided by New Zealand's recent wave of trade agreements. Research limitations/implications: – This study acknowledges the diversity of international marketing strategies between seemingly similar firms by recognising that approaches generally viewed as unlikely to bring success in international markets can work when applied in a particular way and in a particular context. As such the results may offer a useful starting point for the customisation of policy advice on exporting in terms of the context in which SMEs operate. Originality/value: – As well as advancing theoretical perspectives on SME international marketing strategies, the findings are presented as a contribution to the as yet limited evaluation of how SMEs in New Zealand have responded to the emerging opportunities created by FTAs. The interest in filling this gap is part of a growing recognition that factors related to the firm's trading environment have been largely neglected in policy considerations.